Parent-Reported Experience With Pediatric Urology Telemedicine Visits During the COVID-19 Pandemic - Ogundipe, Eniola A.; Caldwell, Brian; Leavitt, Colton; Monnet, Karol; Hedlind, Mikala; Anderson, Alisa; Colby, John; Sevick, Carter J.; Vemulakonda, Vijaya M. (Frontiers in Urology, 2022)
Introduction Telemedicine has had a slow integration into surgical subspecialties like urology. Little data exists on its effect on urologic patient-provider rapport nor long term clinical outcomes. The purpose of this study was to assess the feasibility and parent-reported experience with telemedicine visits in a tertiary pediatric urology practice during the COVID-19 pandemic. Methods Parents/guardians of pediatric urology patients who were seen via telemedicine between March 12th - October 30th, 2020, at Children’s Hospital Colorado main campus or a satellite campus were contacted within 1 week of their child’s visit and invited to take a telephone survey. A total of 4 yes/no questions and an open-ended question was asked to explore domains of the drawbacks and benefits to telemedicine. Categorical responses and associations between parent demographics and telehealth satisfaction were analyzed with descriptive statistics. Open-ended questions were analyzed using a team-based content analysis approach. Results Response rate was 76.7% (376/490). Median patient age was 4 years. 60.9% (229/376) patients were male, and 39.1% (147/376) patients female. 96.5% of parents felt that all their questions were answered by the end of their appointment. 97.8% of parents felt comfortable using telemedicine for future appointments. Patient sex, age, provider type, insurance type, clinic site, distance from clinic site, and visit diagnosis had no significant impact on survey response. Based on open-ended responses, five general themes emerged: issues with accessing technology, time saving logistics, challenging clinical interactions, a positive overall experience, and parents having about a 50/50 split in preference for telemedicine or in person visits. Multiple parents expressed discomfort with a genital exam via telemedicine. Conclusions Overall, parents found telemedicine to be an acceptable alternative to in-person visits and demonstrated a willingness to continue to use it in the future. Patient diagnosis and insurance type had no effect on parent response. Parents noted that pediatric urology offers unique challenges due to its personal and sensitive treatment, including the need to evaluate the genitalia. As the role of telemedicine continues to expand, consideration of these challenges is needed to ensure that pediatric urology patients and their parents are comfortable with this approach.